2011
DOI: 10.1007/s00586-011-1709-6
|View full text |Cite
|
Sign up to set email alerts
|

Leg pain and psychological variables predict outcome 2–3 years after lumbar fusion surgery

Abstract: Prediction studies testing a thorough range of psychological variables in addition to demographic, workrelated and clinical variables are lacking in lumbar fusion surgery research. This prospective cohort study aimed at examining predictions of functional disability, back pain and health-related quality of life (HRQOL) 2-3 years after lumbar fusion by regressing nonlinear relations in a multivariate predictive model of pre-surgical variables. Before and 2-3 years after lumbar fusion surgery, patients completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 43 publications
(43 reference statements)
5
91
1
Order By: Relevance
“…Our results are consistent with previously published studies in both Southern 19 and Northern 2 European patients. In 61 Greek patients undergoing 1-level posterior lumbar spine fusion, Papaioannou et al reported that catastrophizing predicted postoperative pain intensity and analgesic use.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with previously published studies in both Southern 19 and Northern 2 European patients. In 61 Greek patients undergoing 1-level posterior lumbar spine fusion, Papaioannou et al reported that catastrophizing predicted postoperative pain intensity and analgesic use.…”
Section: Discussionsupporting
confidence: 94%
“…Preoperative psychosocial status has shown to be an important factor of outcome on lumbar spine surgery at 6 months and 2-3 year follow-ups (73,128). In the present study, there was, unfortunately, no assessment of participants' psychosocial status, either preoperatively or at early follow-ups.…”
Section: Predicting Long-term Outcomescontrasting
confidence: 47%
“…Patients' expectations of lumbar spine surgery have been measured in various ways, including with standard questions from comprehensive preoperative surveys [2,6,7]. Most studies, however, used ad hoc surveys developed specifically for that study and considered expectations from distinct perspectives, such as likelihood of symptom relief, anticipated time to recovery, and anticipated change in function [2,6,[8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%